Paseo sonoro en el espacio-tiempo - Brown, Andrew (2024)
This article analyzes features of the author’s artistic research in which he investigates space and time through soundwalking, an immersive and embodied practice with the capacity to engage critical attention and reanimate otherwise familiar surroundings. Inspired by social geographer Doreen Massey’s (2005) conception of space as “a simultaneity of stories so far” and “always in the process of being made,” the author’s soundwalks explore the points of intersection at which space is produced. In this paper, the author analyzes the temporal and corporeal aspects of the soundwalking, and their approach based upon an initial capture of sound recordings while walking a particular route, before returning them to be experienced in their original context, thereby exploiting the consequent temporal shift. Through the deliberate blending of these field recordings with the live soundscape during the shared experience of the group soundwalk, perceptions can be destabilized and new relations constructed to the socio‑political realities facing particular communities (LaBelle, 2018). Soundwalks challenge assumptions of present-day lived experience and invite the imagining of alternative pasts and potential futures. The author offers the soundwalk Pentrich Rising – South Wingfield (Brown, 2017) as a case study, sharing insights into their original methodology. Soundwalking is shown to be an effective means of spatio-temporal exploration, with potential to be investigated by researchers from artistic, sonic, spatial, social-historical, socio-political, and environmental disciplines.